Feasibility of cRGD conjugation at 5'-antisense strand of siRNA by phosphodiester linkage extension - Xinyang Zhou; Yufei Pan; Lijia Yu; Jing Wu; Zheng Li; Huantong Li; Zhu Guan; Xinjing Tang; Zhenjun Yang (Elsevier, 2021)
Small interfering RNAs (siRNAs) are widely studied for their highly specific gene silencing activity. However, obstacles remain to the clinical application of siRNAs. Attaching conjugates to siRNAs can improve their stability and broaden their application, and most functional conjugates of siRNAs locate at the 3'-terminus of the sense or antisense strand. In this work, we found that conjugating a group at the 5'-terminus of the antisense strand via phosphodiester was practicable, especially when the group was a flexible moiety such as an alkyl linker. When conjugating a bulky ligand, such as cRGD, the length of the 5'-phosphodiester linker between the ligand and the 5'-terminus of the antisense strand was the key in terms of RNA interference (RNAi). With a relative longer linker, the conjugates showed potency similar to siRNA. A highly efficient transfection system composed of a neutral cytidinyl lipid (DNCA) and a gemini-like cationic lipid (CLD) was employed to deliver siRNAs or their conjugates. The cRGD conjugates showed superior targeting delivery and antitumor efficacy in vivo and also selective cellular uptake in vitro. This unity of encapsulation and conjugation strategy may provide potential strategies for siRNA-based gene therapy.